RNase P cleavage of pseudoknot substrates reveals differences in active site architecture that depend on residue N-1 in the 5’ leader - David M. Kosek; J. Luis Leal; Ema Kikovska-Stojanovska; Guanzhong Mao; Shiying Wu; Samuel C. Flores; Leif A. Kirsebom (RNA Biology)
We show that a small biotin-binding RNA aptamer that folds into a pseudoknot structure acts as a substrate for bacterial RNase P RNA (RPR) with and without the RNase P C5 protein. Cleavage in the single-stranded region in loop 1 was shown to depend on the presence of a RCCA-motif at the 3’ end of the substrate. The nucleobase and the 2’hydroxyl at the position immediately 5’ of the cleavage site contribute to both cleavage efficiency and site selection, where C at this position induces significant cleavage at an alternative site, one base upstream of the main cleavage site. The frequencies of cleavage at these two sites and Mg2+ binding change upon altering the structural topology in the vicinity of the cleavage site as well as by replacing Mg2+ with other divalent metal ions. Modelling studies of RPR in complex with the pseudoknot substrates suggest alternative structural topologies for cleavage at the main and the alternative site and a shift in positioning of Mg2+ that activates the H2O nucleophile. Together, our data are consistent with a model where the organization of the active site structure and positioning of Mg2+ is influenced by the identities of residues at and in the vicinity of the site of cleavage.